Spelling Errors in Thesis of Elementary School Teacher Education Students PGRI Adi Buana University Surabaya Class of 2019 - Nurus Sofiatul Awaliyah; Nur Rohmah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to describe spelling errors at the level of using letters, writing words, and using punctuation marks in the theses of Elementary School Teacher Education students at PGRI Adi Buana University Surabaya class of 2019. This research uses a descriptive qualitative approach with a text analysis method based on the Indonesian Spelling Improved edition V guidelines. The data in this study are words, sentences, and paragraphs that have errors in writing letters, writing words, and writing punctuation in 50 student theses. The most common error is letter writing errors. The amount of data on lettering errors is 672 data, word writing errors are 226 data, and punctuation errors amount to 242 data. The main factors causing these spelling errors include students' lack of understanding of spelling rules, lack of habit of using formal language, and lack of focus of the writer when working on the thesis. Based on these findings, it is recommended that universities provide intensive training related to academic writing of good and correct scientific writing. Students also need to get used to referring to official guidelines (such as EYD edition V) when writing scientific papers, assignments, and reports, so that the work is more professional. Utilize digital tools (such as the halo language application, EYD V, the official website of EYD kemedikbud, etc.) to make it easier to check on good spelling.